KONSTRUKSI PEMIKIRAN SIBAWAIH DALAM KAJIAN IlMU NAHWU - Dihe, Bustamin (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2018)
Sibawaih is one of the nahwu scholars of the Basra school, compiled the science of nahwu in his book known as al-Kitab, he was very careful in selecting the validity of one history, he also did not receive a linguistic argument which was not narrated in mutawatir and linguistic arguments in his book al-Kitab is a book of nahwu which he produces through a very obyektib study, because most of the methods used directly hear the language of the badwi and collect grammar perfectly in his time, and contribute a lot of thought to the reviewers of knowledge in the next generation to understand the language Qur’an as the holy book of Muslims